The Story of Moses - 20160731 frey50; Westman, Tony.; Heston, Charlton; Agamemnon Films; Jones Entertainment Group; GoodTimes Home Video (Firm) (New York : GoodTimes Home Video, 1997)
"Presents the greatest of all epic dramas of the Hebrew bible-- the Book of Exodus"--container. Includes the life of Moses, the deliverance of the Israelites, the parting of the Red Sea, the creation of the Ten Commandments, and the arrival in the promised land.
Hosted by Charlton Heston.
VHS hi fi Dolby surround.
Keywords: Moses; Oral tradition; Israel -- Antiquities